2005
DOI: 10.1111/j.1538-7836.2004.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

A new oral direct thrombin inhibitor, dabigatran etexilate, compared with enoxaparin for prevention of thromboembolic events following total hip or knee replacement: the BISTRO II randomized trial

Abstract: Reilly P for the BISTRO II Study Group. A new oral direct thrombin inhibitor, dabigatran etexilate, compared with enoxaparin for prevention of thromboembolic events following total hip or knee replacement: the BISTRO II randomized trial. J Thromb Haemost 2005; 3:Summary. Background: Dabigatran etexilate is an oral direct thrombin inhibitor undergoing evaluation for the prevention of venous thromboembolism (VTE) following orthopedic surgery. Methods: In a multicenter, parallel-group, double-blind study, 1973 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
293
1
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(315 citation statements)
references
References 14 publications
6
293
1
15
Order By: Relevance
“…Bleeding events tended to occur at the surgical sites. Increased daily doses of dabigatran of 300 mg or greater increased the bleeding rate to 3.8-4.7% without fatalities [35].…”
Section: Clinical Trials With Dabigatranmentioning
confidence: 98%
See 2 more Smart Citations
“…Bleeding events tended to occur at the surgical sites. Increased daily doses of dabigatran of 300 mg or greater increased the bleeding rate to 3.8-4.7% without fatalities [35].…”
Section: Clinical Trials With Dabigatranmentioning
confidence: 98%
“…Five randomized trials have compared dabigatran with enoxaparin for the prevention of VTE in patients undergoing elective orthopedic surgery [31][32][33][34][35]. Between 100 and 450 mg total daily dose of dabigatran was compared to enoxaparin 30 mg twice daily or 40 mg daily.…”
Section: Clinical Trials With Dabigatranmentioning
confidence: 99%
See 1 more Smart Citation
“…CRBE comprised the following: spontaneous skin haematoma greater than 25 cm 2 , wound haematomas greater than 100 cm 2 , spontaneous nose bleed lasting for over five minutes, macroscopic haematuria (spontaneous or lasting for more than 24 hours if associated with an intervention), spontaneous rectal bleeding, gingival bleeding for more than five minutes and any other bleeding event considered as clinically relevant by the investigator. All bleeding events were adjudicated by an independent expert committee blinded to treatment allocations and were categorised as a MBE, CRBE, minor bleeding event or no bleeding event [10,11,15,18]. In this study, we also present the composite of MBE and CRBE, as this was seen as the most informative and relevant bleeding definition for understanding the bleeding profile of drugs used in this investigational setting.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…This pro-drug was in phase II clinical trials for thromboembolism in 1999. It had shown excellent potential as an antithrombotic agent in preclinical studies and it demonstrated an acceptable safety profile for prevention deep vein thrombosis after total hip replacement (Mungall, 2002;Eriksson et al, 2005;Di Nisio et al, 2005). It was the first NOAC; U.S approved in many countries worldwide (in 2010 by the Food and Drug Administration -FDA -and in 2008 by European Medicines Agency -EMA) for the prevention of stroke and blood clots from AF based on the results of the RE-LY (Randomized Evaluation of Long-term Anticoagulant Therapy, Warfarin, compared with Dabigatran) trial (Connolly et al, 2009;Beasley et al, 2011).…”
Section: Historicalmentioning
confidence: 99%